2010
DOI: 10.1093/toxsci/kfq172
|View full text |Cite
|
Sign up to set email alerts
|

Azaspiracid-1 Inhibits Endocytosis of Plasma Membrane Proteins in Epithelial Cells

Abstract: The effect of azaspiracid-1 (AZA-1) on the plasma membrane proteins E-cadherin, Na(+)/K(+)-ATPase, and prolactin receptor (R(prl)) has been investigated in MCF-7 cells. Cell treatment for 24 h with 1nM AZA-1 induced the accumulation of a proteolytic fragment of E-cadherin and significant increases in the levels of Na(+)/K(+)-ATPase and R(prl) at the level of membranous structures. The effect induced by AZA-1 was mimicked by latrunculin A, suggesting that the toxin might act by blocking the endocytosis of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…This effect is consistent with the in vivo effects inducing complete degradation of gastrointestinal lining and confirmed by TEER experiments on monolayer Caco2 model [30] or by disturbance of filament organization in Caco2 cells [31]. Even if some data indicated that AZA1 induced the fragmentation of E-cadherin [21] and inhibited endocytosis [32], its molecular target is still unknown.…”
Section: Dose-response Relationship and Ic 50 Valuessupporting
confidence: 81%
“…This effect is consistent with the in vivo effects inducing complete degradation of gastrointestinal lining and confirmed by TEER experiments on monolayer Caco2 model [30] or by disturbance of filament organization in Caco2 cells [31]. Even if some data indicated that AZA1 induced the fragmentation of E-cadherin [21] and inhibited endocytosis [32], its molecular target is still unknown.…”
Section: Dose-response Relationship and Ic 50 Valuessupporting
confidence: 81%
“…If veratridine/ouabain-treated cells are exposed to Stx, the toxin blocks NaV and sodium entrance, preventing sodium accumulation into neuroblastoma cells and allowing their survival. the knowledge of the mechanism of action of Stx and of cellular physiology, as well as the use of pharmacological tools targeting specific cellular components and processes, has The implications of those findings have supported further studies on the molecular mechanisms of action of Ytx and AZA-groups of compounds, leading to the conclusion that the accumulation of the 100 kDa e-cadherin fragment is caused by inhibition of endocytosis (Callegari, and Rossini, 2008;Bellocci et al, 2010). These specific issues will not be discussed further here; instead we will confine our attention to some heuristic indications provided by those findings that are relevant for the framework of cell-based methods for the detection of toxic agents/stressors.…”
Section: Cell-based Methods For the Detection Of Toxic Agentsmentioning
confidence: 91%
“…In humans, they cause vomiting, nausea, diarrhoea and stomach cramps within a few hours after ingestion (Klontz, Abraham, Plakas, & Dickey, 2009) AZAs target several apoptotic modulators (Botana, et al, 2014;Roman, et al, 2002;Twiner, et al, 2005), such as caspase, cytoskeleton (Vilarino, Nicolaou, Frederick, Vieytes, & Botana, 2007), cytochrome release (Twiner, Hanagriff, Butler, Madhkoor, & Doucette, 2012), c-jun-N-terminal protein kinase (JNK), calcium levels (Cao, LePage, Frederick, Nicolaou, & Murray, 2010;Vale, Wandscheer, et al, 2008), fatty acid biosynthesis (Twiner, et al, 2008). AZAs decrease cell volume mediated by potassium and chloride efflux (Vale, Nicolaou, Frederick, Vieytes, & Botana, 2010), deplete ATP (Kellmann, et al, 2009), inhibit endocytosis (Bellocci, Sala, Callegari, & Rossini, 2010) and decrease procathepsin pools in endocytosis (Sala, Bellocci, Callegari, & Rossini, 2013) (Chevallier, et al, 2015), which could explain the neurotoxicity linked to AZA (Twiner, et al, 2014).…”
Section: Azaspiracid Groupmentioning
confidence: 99%